International consensus definition of low anterior resection syndrome. (10th February 2020) - Keane, C.; Fearnhead, N. S.; Bordeianou, L.; Christensen, P.; Espin Basany, E.; Laurberg, S.; Mellgren, A.; Messick, C.; Orangio, G. R.; Verjee, A.; Wing, K.; Bissett, I.; et al.
Abstract: Aim: Low anterior resection syndrome (LARS) is pragmatically defined as disordered bowel function after rectal resection leading to a detriment in quality of life. This broad characterization does not allow for precise estimates of prevalence. The LARS score was designed as a simple tool for clinical evaluation of LARS. Although the LARS score has good clinical utility, it may not capture all important aspects that patients may experience. The aim of this collaboration was to develop an international consensus definition of LARS that encompasses all aspects of the condition and is informed by all stakeholders. Method: This international patient–provider initiative used an online Delphi survey, regional patient consultation meetings, and an international consensus meeting. Three expert groups participated: patients, surgeons and other health professionals from five regions (Australasia, Denmark, Spain, Great Britain and Ireland, and North America) and in three languages (English, Spanish, and Danish). The primary outcome measured was the priorities for the definition of LARS. Results: Three hundred twenty‐five participants (156 patients) registered. The response rates for successive rounds of the Delphi survey were 86%, 96% and 99%. Eighteen priorities emerged from the Delphi survey. Patient consultation and consensus meetings refined these priorities to eight symptoms and eight consequences that capture essential aspects of the syndrome. Sampling bias may have been present, in particular, in the patient panel because social media was used extensively in recruitment. There was also dominance of the surgical panel at the final consensus meeting despite attempts to mitigate this. Conclusion: This is the first definition of LARS developed with direct input from a large international patient panel. The involvement of patients in all phases has ensured that the definition presented encompasses the vital aspects of the patient experience of LARS. The novel separation of symptoms and consequences may enable greater sensitivity to detect changes in LARS over time and with intervention.